2023
DOI: 10.3390/genes14071407
|View full text |Cite
|
Sign up to set email alerts
|

L138ins Variant of the CFTR Gene in Russian Infertile Men

Abstract: (1) Introduction: Pathogenic variants in the CFTR (Cystic Fibrosis Transmembrane conductance Regulator, OMIM: 602421) gene cause Cystic Fibrosis (CF, OMIM: 219700) and CF-related disorders (CF-RD), often accompanied by obstructive azoospermia due to congenital bilateral aplasia of vas deferens (CBAVD, OMIM: 277180) in male patients. The L138ins (c.413_415dup; p. (Leu138dup)) is a mild variant in the CFTR gene that is relatively common among CF-patients in Slavic populations. The frequency of this variant in Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…In participants (n = 642) from the population-based cohort study ESSE-Vologda, the 394delTT (rs121908769) variant was found to have 0.0047 alleles [20]. This variant of the CFTR gene was found in a large cohort of 6,033 Russian infertile men [14]. However, a heterozygous 394delTT variant was detected in 2 of the 2,146 Russian infertile men examined by Solovyova et al (2018) [21].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In participants (n = 642) from the population-based cohort study ESSE-Vologda, the 394delTT (rs121908769) variant was found to have 0.0047 alleles [20]. This variant of the CFTR gene was found in a large cohort of 6,033 Russian infertile men [14]. However, a heterozygous 394delTT variant was detected in 2 of the 2,146 Russian infertile men examined by Solovyova et al (2018) [21].…”
Section: Discussionmentioning
confidence: 93%
“…Thus, L138ins was found to be the second most common CFTR gene variant in Russian patients with CBAVD syndrome, and the third in prevalence after F508del and CFTRdele2.3(kb) in Russian infertile men. The allele frequency (AF) of this variant in Russian infertile men (n = 6033) was 0.0014 [14]. The L138ins variant was found as compound heterozygous F508del/L138ins in four CBAVD patients (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathogenic CFTR gene variants are a cause of cystic fibrosis (CF, OMIM#219700), and CFTR-related disorders (CFTR-RD). Pathogenic variants of the CFTR gene can result in a congenital bilateral absence of the vas deferens, which could be an isolated syndrome (Congenital Bilateral Aplasia (absence) of the Vas Deferens (CBAVD, OMIM# 277180)) or a clinical feature of CF, leading to obstructive azoospermia in 95% of males with CF [5,6]. Moreover, associations between CFTR variants and other forms of male infertility, namely non-obstructive azoospermia and oligozoospermia, were revealed in a recent meta-analysis [7].…”
Section: Introductionmentioning
confidence: 99%